Lipid phosphatase SHIP‐1 regulates chondrocyte hypertrophy and skeletal development. Issue 2 (9th July 2019) - So, Eui‐Young; Sun, Changqi; Wu, Keith Q.; Driesman, Adam; Leggett, Susan; Isaac, Mauricio; Spangler, Travis; Dubielecka‐Szczerba, Patrycja M.; Reginato, Anthony M.; Liang, Olin D.
Abstract: SH2‐containing inositol‐5′‐phosphatase‐1 (SHIP‐1) controls the phosphatidylinositol‐3′‐kinase (PI3K) initiated signaling pathway by limiting cell membrane recruitment and activation of Akt. Despite the fact that many of the growth factors important to cartilage development and functions are able to activate the PI3K signal transduction pathway, little is known about the role of PI3K signaling in chondrocyte biology and its contribution to mammalian skeletogenesis. Here, we report that the lipid phosphatase SHIP‐1 regulates chondrocyte hypertrophy and skeletal development through its expression in osteochondroprogenitor cells. Global SHIP‐1 knockout led to accelerated chondrocyte hypertrophy and premature formation of the secondary ossification center in the bones of postnatal mice. Drastically higher vascularization and greater number of c‐kit + progenitors associated with sinusoids in the bone marrow also indicated more advanced chondrocyte hypertrophic differentiation in SHIP‐1 knockout mice than in wild‐type mice. In corroboration with the in vivo phenotype, SHIP‐1 deficient PDGFRα + Sca‐1 + osteochondroprogenitor cells exhibited rapid differentiation into hypertrophic chondrocytes under chondrogenic culture conditions in vitro. Furthermore, SHIP‐1 deficiency inhibited hypoxia‐induced cellular activation of Akt and extracellular‐signal‐regulated kinase (Erk) and suppressed hypoxia‐induced cell proliferation. These results suggest that SHIP‐1 is required for hypoxia‐induced growth signaling under physiological hypoxia in the bone marrow. In conclusion, the lipid phosphatase SHIP‐1 regulates skeletal development by modulating chondrogenesis and the hypoxia response of the osteochondroprogenitors during endochondral bone formation. Abstract : In this study, we found that lipid phosphatase SH2‐containing inositol‐5′‐phosphatase‐1 (SHIP‐1) negatively regulates the hypertrophic process of growth plate chondrocytes. SHIP‐1 deficiency accelerates the formation of the secondary ossification center, and SHIP‐1 KO mice have elevated vascularization and more c‐kit + progenitor cells in the bone marrow compartment. SHIP‐1 is also required for hypoxia‐induced Akt/Erk activation and cell proliferation.